Immigration and support for anti-immigrant parties in Europe - Julian Jäger (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2023)
My paper analyzes the link between immigration and support for anti-immigrant parties in Europe. I assemble a unique data set on the share of foreigners for 356 regions in 26 European countries and construct a novel scale for the anti-immigrant position of political parties. I find that Europeans are less supportive of anti-immigrant parties in regions with a higher share of foreigners, consistent with group contact theory. The negative association is driven by Europeans with proredistribution attitudes and is stronger among those with tertiary education, who live in the city, are in the labor force, of younger age, and female. I address several endogeneity concerns, e.g., using a shift-share instrumental variable approach, which provides evidence for a causal channel.
Keywords: D72; J15; Z13; 330; Europe; Immigration; Political preferences